Purification and characterizations of a nanocage ferritin GF1 from oyster (Crassostrea gigas). (June 2020) - Li, Han; Zang, Jiachen; Tan, Xiaoyi; Xia, Xiaoyu; Wang, Zhenyu; Du, Ming
Abstract: Ferritin can form nanocage architectures and has demonstrated potential to serve as functional nanomaterials. Here, the oyster ( Crassostrea gigas ) ferritin gene GF1 was obtained from the viscera of the oyster, successfully cloned, prokaryotically expressed in E. coli BL21 (DE3), purified and characterized. Oyster ferritin was purified by ion exchange chromatography using DEAE-Sepharose Fast Flow. The molecular weight of the subunit was 19972 Da (polyacrylamide gel electrophoresis), and the oyster ferritin weight was 480 kDa (non-denaturing gel electrophoresis). After in-gel trypsin digestion, ferritin was identified using NanoLC-Q-TOF-MS and then analyzed by circular dichroism (CD) spectrometry for its secondary structure. Ferritin nanocages were characterized by dynamic light scattering (DLS) and transmission electron microscopy (TEM). The three-dimensional structure of oyster ferritin was constructed based on the amino acid sequence of human ferritin heavy chain by the homology modeling method. Here, we provide a theoretical foundation for ferritin self-assembly and biological functional activity. Graphical abstract: Image 1 Highlights: The recombinant oyster ferritin was firstly purified and characterized. Oyster ferritin 24 subunits can self-assemble into spherical shells. The three-dimensional structure of subunit and spherical shell was reported.